Preliminary Study: Depriving Piglets of Maternal Feces for the First Seven Days Post-Partum Changes Piglet Physiology and Performance before and after Weaning - Edgar O. Aviles-Rosa; Anoosh Rakhshandeh; John J. McGlone (Animals, 2019)
Coprophagy has been described in piglets although its importance has not been fully assessed. The aim of this study was to evaluate how deprivation of maternal feces influenced piglet physiology, behavior, and performance. Eight litters were randomly assigned to one of two treatments. Control (CON) litters had access to maternal feces while deprived (DEP) litters were deprived of maternal feces for the first 7 d post-partum. Piglet behavior was quantified for 24 h at 7 d of age. Blood samples were collected from one male and female from each litter at 0, 7, and 21 d for hematological analyses, and post-weaning performance was assessed until 123 d post-weaning. No treatment effects were observed on piglet behavior. DEP piglets had 25% lower leukocyte counts (p < 0.01). Relative to DEP litters, CON litters had increased post-weaning feed intake (0.998 vs 0.901 kg/d; p = 0.02) and weight gain (0.536 vs 0.483 kg/d; p < 0.01). At 123 d post-weaning, CON pigs were 9.3 ± 2.3 kg heavier than treatment pigs (p < 0.01). These results suggest that access to maternal feces improves immunocompetence and growth performance. Further studies are needed to explore the physiological mechanisms through which maternal feces improve growth performance, including nutritional and microbial factors, or the presence of maternal semiochemicals.